Treatment patterns, health care resource utilization, and costs in Japanese adults with attention-deficit hyperactivity disorder treated with atomoxetine - Imagawa H (Neuropsychiatric Disease and Treatment, 2018)
Hideyuki Imagawa,1 Saurabh P Nagar,2 William Montgomery,3 Tomomi Nakamura,1 Masayo Sato,1 Keith L Davis2 1Medical Development Unit Japan, Eli Lilly Japan K.K., Kobe, Japan; 2RTI Health Solutions, Research Triangle Park, NC, USA; 3Global Patient Outcomes and Real World Evidence, Eli Lilly Australia, NSW, Australia Objective: To describe the characteristics and medication treatment patterns of adult patients with attention-deficit/hyperactivity disorder (ADHD) prescribed atomoxetine in Japan. Materials and methods: A retrospective analysis of insurance claims data was conducted using the Japan Medical Data Center database. Adults (≥18 years) with ADHD who had ≥1 atomoxetine claim from January 1, 2013 to December 31, 2014, and ≥180 to ≤900 days of follow-up were included. First atomoxetine claim defined the index date. Patient characteristics included age, gender, and comorbid conditions. Treatment patterns assessed included rates of atomoxetine discontinuation, switching, persistence, adherence (assessed via the medication possession ratio), and use of concomitant medications. Results: A total of 457 adults met all the inclusion criteria. Mean (SD) age was 32.7 (10.4) years, and 61.0% of patients were male. Nearly 72.0% of the patients had at least one comorbid mental health condition in the baseline period; depression (43.8%) and insomnia (40.7%) were the most common mental health comorbidities. Most common physical comorbidities were chronic obstructive pulmonary disease (14.4%) and diabetes (12.9%). Non-ADHD-specific psychotropics were prescribed to 59.7% of patients during the baseline period and to 65.9% during the follow-up period; 6.6% were prescribed non-ADHD-specific psychotropics concomitantly with atomoxetine. Overall, 40.0% of adults discontinued atomoxetine during the entire follow-up period and 65.9% were persistent with atomoxetine therapy at 3 months post-index date. Mean (SD) atomoxetine medication possession ratio was 0.57 (0.25), and 25.4% switched to an alternative ADHD therapy; methylphenidate (22.4%) and non-ADHD-specific psychotropics (77.6%) were the most common medication alternatives. Nearly 8% augmented atomoxetine with methylphenidates, non-stimulants, or non-ADHD-specific psychotropics. Conclusion: In this observational study, a majority of adults with ADHD treated with atomoxetine were still persistent with therapy at 3 months post-index date, with one quarter switching to alternative ADHD therapy. High proportions of mental health comorbidities, along with high use of non-ADHD-specific psychotropic medications in both the baseline and follow-up periods, were observed among patients with ADHD prescribed atomoxetine. Keywords: ADHD, atomoxetine, treatment patterns, Japan, comorbidity, claims database, adherence, persistence